Sociolinguistic Profile Research Paper (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research paper provides a comprehensive sociolinguistic analysis of a group of English language learners in Uzbekistan. It delves into various aspects of the learners' backgrounds, motivations, and language proficiency levels. The paper examines the cultural, linguistic, and gender dynamics within the classroom, as well as the broader context in which English is used..